Influence of sucrosis on the degradation of pesticide by white rot fungus (Research, Society and Development, 2021)
The influence of sucrose on the removal of Paraquat (PQT) in synthetic aqueous medium was evaluated by Phanerochaete chrysosporium. Initially, a toxicity test was performed on plates containing paraquat at concentrations of 1, 5, 10, 20 and 30 mg.L-1. Then, they were carried out in batches - agitated batch (RBA) and sequential batch (RBS). Four reactors were submitted, containing medium with 30 mg.L-1 of paraquat, under a reaction time of 144 h, the reactors being RBA-2 and RBS-2 with the addition of 2 gL-1 of sucrose, and without the adding sucrose to the RBA-0 and RBS-0 reactors. In all reactors, paraquat was removed, but in RBS-0, the best mean removal efficiency was obtained (41.1 ± 0.89%). The best values ​​of apparent speed of degradation (k) were found in reactors with sucrose RBA-2 and RBS-2, 0.015 ± 0.002 h-1 and 0.018 ± 0.002 h-1, respectively, indicating that the addition of sucrose influenced the speed removal of paraquat. It was also verified that the pollutant was not completely removed by adsorption to fungal biomass, which microorganisms predominated in the medium at the end of the treatment, demonstrating their role in the paraquat bioremediation process. Therefore, the addition of sucrose influenced the removal speed of the PQT and COD, but not the removal efficiency.